2013
DOI: 10.1371/journal.pone.0057557
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Insight into the Autoimmune Component of Glaucoma: IgG Autoantibody Accumulation and Pro-Inflammatory Conditions in Human Glaucomatous Retina

Abstract: BackgroundThere is accumulating evidence that autoimmune components, such as autoantibodies and autoantibody depositions, play a role in the pathogenesis of neurodegenerative diseases like Alzheimeŕs disease or Multiple Sclerosis. Due to alterations of autoantibody patterns in sera and aqueous humor, an autoimmune component is also assumed in the pathogenesis of glaucoma, a common reason for irreversible blindness worldwide. So far there has been no convincing evidence that autoantibodies are accumulated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 73 publications
4
85
0
4
Order By: Relevance
“…4A) . No other type of immune cell (including B cells or T cells) was found in DBA/2J glaucomatous tissue, although one study has shown B cells in human glaucomatous retinas (Gramlich et al 2013). Monocyte infiltration was apparently blocked by DBA/2J mice treated with radiation ( Fig.…”
Section: Transendothelial Migration Of Leukocytes In Glaucomamentioning
confidence: 92%
“…4A) . No other type of immune cell (including B cells or T cells) was found in DBA/2J glaucomatous tissue, although one study has shown B cells in human glaucomatous retinas (Gramlich et al 2013). Monocyte infiltration was apparently blocked by DBA/2J mice treated with radiation ( Fig.…”
Section: Transendothelial Migration Of Leukocytes In Glaucomamentioning
confidence: 92%
“…In this context, greater prevalence of monoclonal gammapathy has been observed in glaucoma patients, together with higher autoantibody levels in the serum and in the aqueous humor, deposition of immunoglobulins and plasma cells in the retina (Gramlich et al, 2013;Hammam et al, 2008;PinazoDuran et al, 2013;Wax et al, 1998), and chronic activation of resident immunoregulatory glial cells and complement activation (Tezel and The Fourth ARVO/Pfizer Ophthalmics Research Institute Conference Working Group, 2009). Similar to other autoimmune disorders, a serum alteration of the populations of T-cell repertoires and of interleukin-2 receptors has been detected (Yang et al, 2001a).…”
Section: Mechanisms Responsible For Contralateral Eye Involvementmentioning
confidence: 99%
“…TNFα (Tumornekro sefaktorα) und Interleukin (IL)1β, IL6 und IL8 bzw. INFγ (Interferonγ) wa ren erhöht, was darauf hinweist, dass die IgGAntikörperablagerungen in der Reti na in einer proinflammatorischen Umge bung vorliegen [22]. Diese Ergebnisse ste hen so weit im Einklang mit anderen Stu dien zu Zytokinmessungen im Kammer wasser von Glaukompatienten, bei denen die Konzentrationen verschiedener Inter leukine wie CXCL8 ["chemokine (CXC motif) ligand 8" oder IL8], VEGF ("va scular endothelial growth factor"), IFNγ, IL12 und CXCL9 (Monokine indiziert von γInterferon, MIG) stark erhöht vor lagen [23].…”
Section: Inflammation Mikroglia Und Neurodegenerationunclassified
“…Sie werden maßgeblich dar über moduliert und können andererseits beide Chemokine selbst sezernieren. Eine Aktivierung des Komplementsystems in glaukomatösen Retinae konnte bereits nachgewiesen werden [22]. Beim experi mentellen Glaukom im Tiermodell konn te gezeigt werden, dass der degenerative Verlust von retinalen Ganglienzellen mit einer verstärkten Expression von Kompo nenten (C1q und C3) der Komplement kaskade einhergeht und dass eine Inak tivierung dieser Kaskade den Ganglien zellverlust verlangsamen kann [29].…”
Section: Introductionunclassified
See 1 more Smart Citation